Morphological and genetic diversity of Cercospora beticola Sacc isolates in Morocco. (2nd October 2021) - El Housni, Zakariae; Tahiri, Abdessalem; Radouane, Nabil; Ezrari, Said; Ouijja, Abderrahman
Abstract: Cercospora Leaf Spot is the most important foliar disease that affects sugar beet crops all over the world. The recent study focuses on the effect of isolation methods, light, and the culture medium on the development of Cercospora beticola Sacc. The results underlined that abundant sporulation occurred in the alternating 12-hr light/dark, but few spores were produced in the continuous darkness. The two medium PDA and SBLEA had no statistically significant effect on sporulation rate or fungal speed growth. From four isolation techniques, only the scraping by scalpel pseudostromata on old dry leaf technique has a lower rate of growth and had no sporulation in the tow media and under the tow light regime. Also, isolates collected from the four major sugar beet cultivating agro-ecologies (Gharb; Doukkala; Tadla; Moulouya), over two growing seasons (2017–2018), were characterized according to morphological and genetic traits. The genetic difference was studied by four RAPD primers and three DAMD. The outcome resulted in high band diversity depending on the used primer even for isolates from the same beet production area. The isolates showed a high diversity of morphological and molecular traits and the comparison between the classification of the two diversities did not reveal any connection between genetic and morphological diversity. Further studies may explore the source of this high genetic diversity, such as long infected seed transmission or C. beticola mycelium anastomosis.